2006
DOI: 10.1590/s0101-81752006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento do boto-cinza, Sotalia guianensis (Van Bénédén) (Cetacea, Delphinidae) na presença de barcos de turismo na Praia de Pipa, Rio Grande do Norte, Brasil

Abstract: Revista Brasileira de Zoologia 23 (3): 661-666, setembro, 2006Entre as mais variadas modalidades de ecoturismo, um deles, voltado para avistagem de mamíferos aquáticos, principalmente golfinhos e baleias, têm mostrado grande potencial de crescimento. O Comitê Científico da International Whaling Comission (IWC) considerando o desenvolvimento acelerado do turismo de observação de baleias e golfinhos e seu inegável benefício econômico (WILLIAMS et al. 2002), desenvolveu diretrizes para sua regulação estabelecendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…No absence of a reaction was seen in any of the meetings where the boat got too close; the animals reacted by, principally, trying to withdraw from the boat. Withdrawing reactions during interaction with the boats were also observed for the estuarine dolphins at the Curral Beach (RN) and were interpreted as being a defence behaviour, through which the animals seek protection, especially for the young, by moving far away (Santos-Jr et al, 2006). This same understanding can also be applied to the animals studied here.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…No absence of a reaction was seen in any of the meetings where the boat got too close; the animals reacted by, principally, trying to withdraw from the boat. Withdrawing reactions during interaction with the boats were also observed for the estuarine dolphins at the Curral Beach (RN) and were interpreted as being a defence behaviour, through which the animals seek protection, especially for the young, by moving far away (Santos-Jr et al, 2006). This same understanding can also be applied to the animals studied here.…”
Section: Discussionsupporting
confidence: 56%
“…Possible impacts from estuarine dolphin watching have already been studied at the Pipa beach (Rio Grande do Norte State) on the north-east Brazilian coast (Valle and Melo, 2006;Santos-Jr et al, 2006), who verified that the animals changed their behaviour when boats approached. In the EPA (Environment Protection Area) of Anhatomirim (Santa Catarina State, south of Brazil), the number of tourists looking for schooner trips grew more than 140% from 1993 to 2001 (Mori, 2002), the situation is compounded by the fact that only 29% of this EPA, created in 1992, is today used by the dolphins and 58% of the area occupied by these animals is outside the delimited area (Wedekin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that the reactions were neutral because the speed and direction of the boats were constant. All reports of S. guianensis interactions and observations from tourist boats reported negative reactions by the dolphins (Santos Jr. et al, 2006;Valle & Melo, 2006;Pereira et al, 2007;Tosi & Ferreira, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Research on the interaction between S. guianensis and boats, has been performed along the Brazilian coast (Santos-Jr. et al, 2006;Valle & Melo, 2006;Pereira et al, 2007;Araújo et al, 2008;Carrera et al, 2008;Filla et al, 2008;Tosi & Ferreira, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such environments provide sightings of humpback whale (Megaptera novaeangliae) in Abrolhos Marine National Park (State of Bahia); bottlenose dolphin (Tursiops truncatus) in Laguna (State of Santa Catarina); right whale (Eubalaena australis) in southern parts of the State of Santa Catarina; Guiana dolphin (Sotalia guianensis) in Anhatomirim Environmental Protection Area (APA) (State of Santa Catarina), and the spinner dolphin (Stenella longirostris) in Fernando de Noronha (FN) archipelago (State of Pernambuco). Nowadays, those are still the primary regions for watching activity in the country, adding the current watching tourism of Inia geoffrensis in Novo Airão in the Amazon Basin (State of Amazonas) (Romagnoli et al 2011) and Guiana dolphin (Sotalia guianensis) in Pipa Beach (State of Rio Grande do Norte) (SantosJr. et al, 2006).…”
Section: Introductionmentioning
confidence: 99%